Investigation of laboratory and field tests of piles installed by displacement technology - Zhussupbekov, A.Zh.; Omarov, A.R.; Dhanya, J.S.; Isakulov, A.B.; Iskakov, S.B. (Eurasian Journal of Applied Engineering and Technology (EJAET), 2023)
When compared to conventional pile systems, the Drilled Displacement System (DDS) and Continuous Flight Auger (CFA) piles offer advantages in terms of improved load-carrying capacity, quicker installation, and less spoil generation. In this article, experiments on miniature piles built utilizing the Drilled Displacement System (DDS) and Continuous Flight Auger (CFA) technologies in a soil-filled test tank are described. For the study, model piles with dimensions of 20 mm in diameter and 300 mm in length were used, scaled at 1/20. The model piles are subjected to static loading, and throughout each phase of the loading process, the relevant displacements are measured. For both DDS and CFA piles, the analysis's findings on load-settlement curves and estimates of ultimate bearing capacity were compared. According to the study, the DDS piles outperformed the CFA piles in terms of load-carrying capacity. Additionally, full-scale field tests with static loads were performed on DDS-drilled piles with dimensions of 400 mm in diameter and 6 m in length. The field test's load-settlement response exhibits good agreement with the model testing. Overall, the study's findings offer insightful information about the behavior and performance of DDS piles that may be used to improve the design and installation of these piles in various soil types.